2021
DOI: 10.31083/j.jin2004100
|View full text |Cite
|
Sign up to set email alerts
|

Altered cortical activity in patients with lower limb amputation based on EEG microstate

Abstract: Previous studies have revealed significant changes in electroencephalogram (EEG) microstates in neuropsychiatric diseases, including schizophrenia, depression, and dementia. To explore the restingstate EEG microstate with amputation, we collected the EEG datasets from 15 patients with lower limb amputation and 20 healthy controls. Then, we analyzed the parameters of four classical EEG microstates (A-D) between the two groups. Specifically, the parameters were statistically analyzed, including duration, occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…11 Moreover, several studies have reported abnormalities of temporal microstate characteristics in patients with chronic low back pain, fibromyalgia, and phantom limb pain. 12,13,14 For example, temporal characteristics, such as the duration of one microstate, were shown to be decreased in chronic low back pain patients. 12 However, there have not been any studies that have analyzed EEG microstates in patients with CRPS.…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, several studies have reported abnormalities of temporal microstate characteristics in patients with chronic low back pain, fibromyalgia, and phantom limb pain. 12,13,14 For example, temporal characteristics, such as the duration of one microstate, were shown to be decreased in chronic low back pain patients. 12 However, there have not been any studies that have analyzed EEG microstates in patients with CRPS.…”
Section: Introductionmentioning
confidence: 99%